Phenobarbital induced Stevens–Johnson syndrome in a child - Gaur, Sumit (Medknow Publications & Media Pvt Ltd, 2012)
Phenobarbital, an antiepileptic agent has numerous adverse reactions including Stevens– Johnson syndrome (SJS), a rare medical emergency. A 12-year-old male epileptic child with phenobarbital-induced SJS was referred for the management of severe pain in relation to extensively decayed molar tooth and oral mucosal ulcerations. The patient was managed by withdrawal of phenobarbital and palliative treatment of the lesions.